2018
DOI: 10.1111/jcmm.13887
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐130b promotes the progression of oesophageal squamous cell carcinoma by targeting SASH1

Abstract: MiR‐130b and SAM and SH3 domain containing 1 (SASH1) play an important role in many types of human cancers. The aim of our research was to study their interactions in the process of the proliferation and aggressiveness of oesophageal squamous cell carcinoma (ESCC) cells. Microarray analysis was done to screen the differentially expressed genes in the ESCC tissues. miR‐130b and SASH1 mRNA levels in the ESCC tissues and cells were detected by qRT‐PCR. Dual luciferase reporter system was used to verify the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Due to late diagnosis, recurrence and metastasis, the overall survival time of patients with ESCC is not satisfactory (1,4). Therefore it is important to identify the molecular mechanisms and develop novel strategies for ESCC therapy (5,6). Recently, some oncogenes have been reported to be responsible for the growth and metastasis of ESCC, and some of them have been suggested to be potential therapeutic targets (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Due to late diagnosis, recurrence and metastasis, the overall survival time of patients with ESCC is not satisfactory (1,4). Therefore it is important to identify the molecular mechanisms and develop novel strategies for ESCC therapy (5,6). Recently, some oncogenes have been reported to be responsible for the growth and metastasis of ESCC, and some of them have been suggested to be potential therapeutic targets (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…7 SASH1 deficiency was also associated with the increased proliferation and aggressiveness of oesophageal squamous cell carcinoma (ESCC) cells. 19 In addition, the inhibition of SASH1 by miR-17 is involved in the increased cell proliferation, migration and the decreased cell apoptosis in osteosarcoma cells. 20 Thus, SASM1 is closely correlated with the development and progression of tumors and could be regarded as a promising marker for diagnosis and prognosis of malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In our recently published paper, we investigated miR-124-5p, which existed in MSCs-conditioned medium, and found that the miR-124-5p was involved in the regulation of MSCs-conditioned medium in LPS-induced ALI by targeting α-ENaC [19]. Related studies have shown that miR-130b in MSCs can regulate the inflammatory response, cell function and gene expression of various diseases [20][21][22], whereas its role in ALI and the relative mechanisms are seldom studied. Therefore, we chose miR-130b as our main research object and co-cultured with AT2 cells to explore its role in the regulation of MSCs in LPS-induced ALI, aiming to provide a novel direction for therapeutic strategy in ALI.…”
Section: Introductionmentioning
confidence: 99%